Unmistakable impact a partnership approach for dramatically improving instruction - Knight, Jim.; Sage eBooks; Learning Forward (Thousand Oaks, Calif. : Corwin ; London : SAGE, 2011)
A staggering amount of evidence shows that our schools are not as effective as they should be, and they are working toward improvement. This book simplifies the process for becoming an Impact School through targeted, consistent professional learning that is done with teachers, not to teachers.
Published in association with LearningForward.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Teachers -- In-service training -- United States; School improvement programs -- United States; Electronic books